Progress in researches on methodology of disability weight - Kui-ru HU; Xia WAN (Editorial Office of Chinese Journal of Public Health, 2022)
Disability weight (DW), one of important indicators for estimating disability-adjusted life years (DALY), represents the severity of health loss in a particular disability state. Currently, DW has two sets of methodology named as "disability weight from the Global Burden of Disease Study" (GBD DW) and "health status weight from Health-Related Quality of Life" (HRQOL HSW). In order to promote the further development of DW methodology, this study briefly reviewed and compared these two sets of methodological study, including the respondents for the assessment, definition of health status, assessment methods and the methods' strength and weakness, which would provide a comprehensive reference for the improvement of DW research.